THE EFFECT OF THE APPLICATION OF GARDENING MODALITY THERAPY ON THE QUALITY OF LIFE OF THE OLDER PEOPLE - Ariesti, Ellia; Sutiyarsih, Emy; Sulartri, Anastasia Sri (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2024)
Background: Humans experience the natural process of aging. The most important stage is in the old or elderly stage, where a person naturally experiences changes and decreases in conditions from physical, social, psychosocial. One way to optimize the cognitive function of the elderly is to use modality therapy. One type of modality therapy is gardening, gardening activities can provide opportunities for the elderly to do physical activity, release physical energy and emphasize physical movements. Objectives: This study aimed to analyze the effect of the application of gardening modality therapy on the quality of life of the older people in Puskesmas Tajinan Malang Regency. Methods: The design used quasi-experimental with one group pre-posttest design. The population in this study were all old people who participated in prolanis activities and were aged > 50 years totaling 30 people. This research was conducted for one month. Measurement of the quality of life of the elderly used the WHOQOL-BREF questionnaire, while for the measurement of gardening therapy used an observation sheet. Data analysis was carried out using the statistical test used was the Wilcoxon Test with α 0.05. Results: The results of bivariate analysis using the Wilcoxon test show that the P value is 0.317 > 0.05, which means that there is no significant effect of providing gardening modality therapy 2 times per week on the quality of life of the older people, while the provision of gardening modality therapy 3 times per week on the quality of life of the older people the results of bivariate analysis using the Wilcoxon test show that the P value is 0.0001 < 0.05, which means there is a significant effect. Conclusion: The effect of gardening therapy on the quality of life of the elderly can be used as an alternative to improve the quality of life of the elderly, because gardening can make the elderly more productive, the elderly can also be a stimulation for the elderly to socialize and do physical activity.